Social networks research in ex situ populations: Patterns, trends, and future directions for conservation‐focused behavioral research - Lewton, Jack; Rose, Paul E. (Zoo biology, 2021)
Social networks research using non‐human animals has grown over the past decade, utilizing a wide range of species to answer an array of pure and applied questions. Network approaches have relevance to conservation, evaluating social influences on fecundity, health, fitness and longevity. While the application of network approaches to in situ populations with conservation concern appears in published literature, the degree to which ex situ and zoo‐housed populations are the focus of “social networks for conservation research” is limited. Captive environments provide scientists with an ability to understand the social behavior of species that may be hard to observe consistently in the wild. This paper evaluates the scope of network research involving ex situ populations, analyzing output from 2010 to 2019 to determine trends in questions and subjects using ex situ populations. We show that only 8.2% of ex situ social network analysis (SNA) implications are of conservation‐focus, apparent in papers relating to birds, carnivores, bats, primates, reptiles, and ungulates. Husbandry and welfare questions predominate in ex situ network research, but over half of these papers have nonpractical application (basic science). The chance of a citation for a basic science paper was 95.4% more than for a conservation‐based paper. For taxonomic groups, primate‐focused papers had the most citations. The focus of ex situ conservation‐based networks research may be driven by the needs of conservation programs (e.g., population recovery outcomes) or by a need to evaluate the efficacy of ex situ conservation goals. We evaluate our findings considering the IUCN's One Plan Approach to conservation to show how in situ and ex situ network research is applicable to global conservation efforts. We have identified that there is a lack of application and evaluation of SNA to wildlife conservation. We highlight future areas of research in zoos and hope to stimulate discussion and collaboration between relevant parties. Social network research papers that feature zoo and aquarium populations can be lacked in a conservation evidence theme or aim, focussing more on basic science (nonpractical application papers) or evidence to inform welfare and husbandry. Zoo and aquarium populations are excellent tools for conservation themed social networks research and could be utilized more frequently for such studies. Highlights Social network research on ex situ animal populations can directly inform conservation initiatives. We find that there is little application of conservation within zoo‐focussed social network analysis (SNA) research and most papers had no practical application (basic science). Taxonomic analyses show that primate papers dominate the zoo‐focussed SNA literature. The chances of a citation for a conservation focused paper is 95% less than for a nonapplication (basic science) paper. Social networks approaches can help underpin One Plan Approach initiates at a species and population level by helping support collection planning. Zoo populations should be used more as a resource for this behavioral research to further our understanding of conservation outcomes.